Alterations in Whey Protein Abundance Correlated with the Somatic Cell Count Identified via Label-Free and Selected Reaction Monitoring Proteomic Approaches - Jing Li; Kaixu Chen; Changjiang Zang; Xiaowei Zhao; Zhiqiang Cheng; Xiaobin Li; Caidie Wang; Yong Chen; Kailun Yang (Animals)
The somatic cell count (SCC) is widely used to assess milk quality and diagnose intramammary infections. Several whey proteins have been shown to correlate significantly with SCC and are considered potential indicators of udder health. However, the relationship between milk whey proteins and SCC has not been fully elucidated. In this study, milk samples were grouped into five categories based on SCC levels. Subsequently, whey proteins were identified using a label-free proteomics approach, and the differential abundance of proteins was validated through a selected reaction monitoring (SRM) method. The levels of various proteins, including azurocidin 1 and kininogen-2, exhibited an increase, whereas topoisomerase I, tropomyosin-1, and desmin showed a significant decrease depending on the SCCs. Principal component analysis unveiled that these proteins contributed to the developmental alterations in milk proteins. A majority of these differentially abundant proteins were associated with response to stimulus, localization, and defense response. Our results provide fundamental information on the SCC that can be utilized for evaluating milk quality and serve as potential indicators for detecting intramammary infections.